Effect of pretreatment and enzymatic hydrolysis on the physical-chemical composition and morphologic structure of sugarcane bagasse and sugarcane straw - Moretti, Marcia Maria de Souza [UNESP]; Perrone, Olavo Micali [UNESP]; Nunes, Christiane da Costa Carreira [UNESP]; Taboga, Sebastião [UNESP]; Boscolo, Maurício [UNESP]; da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP] (Elsevier, 2016)
The present work aimed to study the effect of the pretreatment of sugarcane bagasse and straw with microwave irradiation in aqueous and acid glycerol solutions on their chemical composition, fiber structure and the efficiency of subsequent enzymatic hydrolysis. Thermogravimetric analysis showed that the pretreatment acted mainly on the lignin and hemicellulose fractions of the bagasse, whereas, in the straw, lesser structural and chemical changes were observed. The images from transmission electron microscopy (TEM) revealed that treating bagasse and straw with acid glycerol solution loosened the cell walls and there was a breakdown in the pit membrane. The treated material was submitted to hydrolysis for 72 h and higher yields of reducing sugars were observed compared to the untreated material (250.9 mg/g from straw and 197.4 mg/g from bagasse). TEM images after hydrolysis confirmed the possible points of access of the enzymes to the secondary cell wall region of the pretreated biomass.
Keywords: Glycerol; Microwave; Pretreatment; Saccharification; Sugarcane biomass; Sulfuric acid